Biophysical characterization of the underappreciated and important relationship between heart rate variability and heart rate - Monfredi, Oliver; Lyashkov, Alexey E; Johnsen, Anne-Berit; Inada, Shin; Schneider, Heiko; Wang, Ruoxi; Nirmalan, Mahesh; Wisloff, Ulrik; Maltsev, Victor A; Lakatta, Edward G; Zhang, Henggui; Boyett, Mark R (Hypertension (Dallas, Tex. 1979), 2014)
Heart rate (HR) variability (HRV; beat-to-beat changes in the R-wave to R-wave interval) has attracted considerable attention during the past 30+ years (PubMed currently lists >17 000 publications). Clinically, a decrease in HRV is correlated to higher morbidity and mortality in diverse conditions, from heart disease to fetal distress. It is usually attributed to fluctuation in cardiac autonomic nerve activity. We calculated HRV parameters from a variety of cardiac preparations (including humans, living animals, Langendorff-perfused heart, and single sinoatrial nodal cell) in diverse species, combining this with data from previously published articles. We show that regardless of conditions, there is a universal exponential decay-like relationship between HRV and HR. Using 2 biophysical models, we develop a theory for this and confirm that HRV is primarily dependent on HR and cannot be used in any simple way to assess autonomic nerve activity to the heart. We suggest that the correlation between a change in HRV and altered morbidity and mortality is substantially attributable to the concurrent change in HR. This calls for re-evaluation of the findings from many articles that have not adjusted properly or at all for HR differences when comparing HRV in multiple circumstances.